2015
DOI: 10.1111/pace.12656
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of a Very Prolonged Asystole during Head‐Up Tilt Test

Abstract: A retrospective study was conducted in two centers between January 2003 and December 2013 and included a total of 2,263 consecutive HUT tests (sensitized with isosorbide dinitrate) performed in 2,247 patients with syncope of unknown etiology. Cardioinhibitory response with asystole was observed in 149 (6.6%) of these tests (44.3% women, mean age 37 ± 18 years old, 16.1% in the nonpharmacological phase), with a median duration of asystole of 10 (6-19) seconds. Very prolonged asystole (≥30 seconds) was documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
2
7
0
1
Order By: Relevance
“…Regarding the clinical profile of the case series of the present study, 9.2% of the patients submitted to TT had cardioinhibitory response, an incidence in accordance to those in the literature: up to 6.6%, considering only the passive phase, 28 or up to 21% in sensitized protocols. 7-9 Trauma secondary to syncope occurred in 20% of the case group with exclusively vasovagal syncope, while in the literature that ranged from 27.5% to 29% in a heterogeneous group (vasovagal and of unexplained origin).…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the clinical profile of the case series of the present study, 9.2% of the patients submitted to TT had cardioinhibitory response, an incidence in accordance to those in the literature: up to 6.6%, considering only the passive phase, 28 or up to 21% in sensitized protocols. 7-9 Trauma secondary to syncope occurred in 20% of the case group with exclusively vasovagal syncope, while in the literature that ranged from 27.5% to 29% in a heterogeneous group (vasovagal and of unexplained origin).…”
Section: Discussionsupporting
confidence: 89%
“…The mean asystole duration in our cohort, with or without seizure, was similar to that reported previously for asystole followed by seizure (12.8 s) (23). Some studies have shown that the average age (range 21-47 years) for syncope without asystole is higher than syncope with asystole (15-32 years) (23)(24)(25)(26). Our data does not corroborate this relationship of complex VVS with age, though male gender increases the predisposition to complex syncope, that is, SySz.…”
Section: Discussionsupporting
confidence: 85%
“…The second alignment was performed based on asystole duration. The cutoff value was 30 s according to cardiac electrophysiology literature, where vagally induced asystole >30 s was labeled “very prolonged” and “malignant.” We aimed to test whether the presence of a “very prolonged” IA (>30 s) was characteristic for different or more severe seizures.…”
Section: Methodsmentioning
confidence: 99%